2011
DOI: 10.1097/qad.0b013e32834bfde9
|View full text |Cite
|
Sign up to set email alerts
|

Demographic but not geographic insularity in HIV transmission among young black MSM

Abstract: Phylogenetic clusters involving HIV-infected young black MSM were homogeneous with respect to demographic and risk characteristics, suggesting insularity of this population with respect to HIV transmission, but were geographically heterogeneous. Reducing HIV transmission among young black MSM in Mississippi may require prevention strategies that are tailored to young black MSM and those in their sexual networks, and prevention interventions should be delivered in a manner to reach young black MSM throughout th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
53
2

Year Published

2012
2012
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 50 publications
(61 citation statements)
references
References 19 publications
6
53
2
Order By: Relevance
“…15,18,19 Here, we found that by including sequences representing the global diversity of HIV, we were able to infer indirect connections between persons within the United States through one or more international sequences. This finding demonstrates the added benefit of including the global diversity of HIV in transmission network analyses, even if the aim of an analysis is local in scope (as suggested by Wertheim et al…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…15,18,19 Here, we found that by including sequences representing the global diversity of HIV, we were able to infer indirect connections between persons within the United States through one or more international sequences. This finding demonstrates the added benefit of including the global diversity of HIV in transmission network analyses, even if the aim of an analysis is local in scope (as suggested by Wertheim et al…”
Section: Discussionmentioning
confidence: 85%
“…20 In a public health setting, demographics and transmission category may assist in identifying groups of highest priority for targeted intervention. 18,30,31 Given the ability of HIV to spread across large geographic distances and establish onward transmission clusters, these surveillance efforts should be broad in scope.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Based on findings from the rapid assessment, CDC and MSDH incorporated an in-depth qualitative interview component into their broader investigation, which also included a casecontrol study, 20,21 a phylogenetic analysis, 22 and a network analysis. 23 In the present study, we analyzed data from the qualitative interviews with HIV-infected and HIV-uninfected young black MSM to explore the role of community, religious, and familial influence on the experiences of young black MSM.…”
Section: Introductionmentioning
confidence: 99%
“…Previous research examining the role of age and racial dynamics in the sexual networks of young MSM relied on small sample sizes [2,3,4,5,7,8] or survey data [4,8]. Whereas survey data can provide information about social and sexual networks, identifying genetically highly similar HIV sequences can allow us to infer HIV transmission networks and describe transmission between the persons within these networks [10][11][12][13][14][15][16][17][18][19]. In an effort to better understand the role that age and race/ethnicity of sexual partners may play in HIV acquisition for young MSM, we used HIV sequence data reported to U.S. National HIV Surveillance System (NHSS) to investigate HIV transmission dynamics for young MSM.…”
Section: Introductionmentioning
confidence: 99%